DEVELOPMENT OF APPRAISAL SYSTEM TO IMPROVE MILITARY OFFICERS PERFORMANCE ASSESSMENT PROCESS - Wahyudi Agustiono (JOURNAL ASRO, 2018)
This paper at hand is aimed at describing the experience of developing a decision support system used for assessing employee performance. Taking into account the distinctive nature of the military organization that is rigorous, traditional, hierarchical, controlled, bureaucratic, and conservative; this study shows the complexity and challenges when it comes to design and developing the appraisal system. In view of the unique nature of the military organization in performing the appraisal process, this study sought various methods and techniques that could guide the development process. The experimental results suggest how the waterfall model was useful to guide the development process. In developing the appraisal system, this study shows how the Simple Multi-Attribute Rating Technique (SMART) and Representation Operation Memory and Control aids (ROMC) are useful conception. Finally, this study concludes how the selection appropriate approach, method and techniques contribute is critical to successfully the development of appraisal system, especially in a military organization that is considered as unique